Investigations into some effects of cysteine administration to the New Zealand Romney : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Scienc - Dryden, Gordon McLean (Massey University, 1968)
The Present Work: Up to this date, all sulphur containing amino-acid and protein infusion work had been done in Australia using Australian Merinos. It was decided to conduct a similar experiment to see whether cysteine infusion had a similar effect on the wool grovvth rate of New Zealand Romneys. The work described in this thesis consists of two parts:- (i) a preliminary experiment was conducted to see if the Romney wool growth rate responded to cysteine infusion, and if so, at what dose levels. A first investigation of the wool factors involved was also made. (ii) having found that the Romney did respond to cysteine treatment a second experiment was carried out to determine more exactly the wool factors involved in the response and to see if the response was altered by the protein content of the basal diet. The effect of cysteine administration on the digestibility of basal diet was also examined. [From the Introduction]
Keywords: Romney marsh sheep; Cystathionine gamma-lyase